Influence of Hydraulic Conditions on Reclaimed Water Polishing Using Soil and Sand Columns - Silva, Flora; Maria Antão-Geraldes, Ana; Scalize, Paulo; Cavaleiro, Victor; Albuquerque, António (KnE Materials Science, 2022)
The removal of residual pollutants from a synthetic effluent with a composition similar to that of urban effluent from secondary treatment was evaluated in vertical downflow columns. These were filled with soil, the fine fraction of the soil, and sand, and operated in discontinuous and continuous mode. The results showed high removal rates of organic matter, ammonium, nitrate and phosphate in the discontinuous and continuous experiments, especially for the fine fraction. Therefore, the soil is suitable for removing organic matter and nutrients (N-NH4, N-NO3, and P-PO4), and can be used for polishing wastewater before its infiltration. Keywords: wastewater reuse, organics removal, nutrient removal, residual soil, river sand